Otoacoustic emission examination results on down syndrome students - Fasya, Haidar Haikal; Lestari, Rahmi; Hafiz, Al; Asyari, Ade; Masnadi, Nice Rachmawati; Ilmiawati, Cimi (PERHATI-KL, 2023)
Background: Down syndrome (DS) is a genetic disorder that occurs due to an excess of genetic material on chromosome 21. Down syndrome was associated with various congenital abnormalities and dysfunction of several organs, one of which was hearing. DS patients often experience sensorineural hearing loss. Evaluation of sensorineural hearing loss in DS patients could be done in several ways, one of which is the Otoacoustic Emission (OAE) examination. Purpose: This study aimed to describe the results of the OAE examination in elementary school children at special need schools in Padang City in 2022. Methods: This research was a descriptive study, using a cross sectional study design. Data were collected and processed using consecutive sampling technique. The research subjects who met the criteria were 31 samples. Results: The results showed that the majority of DS subjects received “refer” results 25/31 on OAE examination, OAE “refer” results occurred both in one ear or both ears. The “refer” results of the OAE were greater in male DS patients 20/24 than female 5/7 and more common in the 18-21 year old age group. Conclusion: Conclusions based on this study, people with DS are more at risk of having sensorineural hearing loss.